2019
DOI: 10.12669/pjms.35.5.310
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy in combination with surgery in the treatment of local advanced breast cancer

Abstract: Objective: To investigate the effect of neoadjuvant chemotherapy combined with surgery on locally advanced breast cancer and its prognosis. Methods: One hundred and fifty-four patients with locally advanced breast cancer who were admitted to our hospital from February 2014 to April 2015 were selected as the study subjects. They were divided into an observation group and a control group according to the principle of random equalization, 77 each group. The observation group was treated with TAC scheme, neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Also in the study by Li, L, et al (2018) on breast cancer patients, the mean age of patients was higher than the mean age of the present study however, there was no significant difference between the two treatment groups in terms of mean age (13), which is also consistent with the results of the present study. The mean duration of surgery in the two treatment groups was 72 and 73 minutes while this time was obtained in the study of et al Haixia Zhao (2015) in two groups of 43 and 58 minutes (14), which is higher than the average duration of surgery in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Also in the study by Li, L, et al (2018) on breast cancer patients, the mean age of patients was higher than the mean age of the present study however, there was no significant difference between the two treatment groups in terms of mean age (13), which is also consistent with the results of the present study. The mean duration of surgery in the two treatment groups was 72 and 73 minutes while this time was obtained in the study of et al Haixia Zhao (2015) in two groups of 43 and 58 minutes (14), which is higher than the average duration of surgery in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Regarding surgery duration, two studies [25,27] favoured NACT and two studies [23,28] favoured the control group, but overall there was no difference between the two groups. These results are supported by Schaverien et al [47] in a prospective study on breast cancer patients which showed a non-significant trend towards a higher rate of multiple complications in patients treated with NACT compared to those who were not, and found no difference in surgery duration between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The study was not included in the meta-analysis because follow-up was not defined. In terms of blood loss, two studies [25,27] favoured NACT while one study [38] favoured the control group. Although the difference in blood loss was found to be significant, favouring NACT over the control group, it should be interpreted cautiously as only three studies were included in the analysis providing a low power.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is generally believed that pathological complete remission after neoadjuvant chemotherapy is closely related to the disease-free survival and overall survival of breast cancer patients. Patients with complete pathological remission often have a better prognosis [11,12].…”
Section: Introductionmentioning
confidence: 99%